2018
DOI: 10.1002/ange.201708879
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Driven Water Splitting Mediated by Photogenerated Bromine

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The product was isolated as a yellow solid (0.05 g, 0.046 mmol, 12% yield). 1 (6). To a flame-dried flask were added 4-(5-(2ethylhexyl)-4,6-dioxo-5,6-dihydro-4H-thieno [3,4-c]pyrrol-1-yl)benzaldehyde (7) (0.100 g, 0.27 mmol, 5′-chloro-2,2″,4,4″-tetrakis-(hexyloxy)-1,1′:3′,1″-terphenyl (D-Cl) (0.197 g, 0.29 mmol), and toluene (2.7 mL, 0.1 M).…”
Section: Methodsmentioning
confidence: 99%
“…The product was isolated as a yellow solid (0.05 g, 0.046 mmol, 12% yield). 1 (6). To a flame-dried flask were added 4-(5-(2ethylhexyl)-4,6-dioxo-5,6-dihydro-4H-thieno [3,4-c]pyrrol-1-yl)benzaldehyde (7) (0.100 g, 0.27 mmol, 5′-chloro-2,2″,4,4″-tetrakis-(hexyloxy)-1,1′:3′,1″-terphenyl (D-Cl) (0.197 g, 0.29 mmol), and toluene (2.7 mL, 0.1 M).…”
Section: Methodsmentioning
confidence: 99%
“…Althoughm ost studies of DSPsh ave been conducted in the presence of sacrificial electron donators to promote the water-splittingh alf reaction, [30][31][32][33][34][35] there have been several reports concerning water reduction or overallw ater splitting in the presence of redox-reversible electron mediators. [36,37] In 1993,M allouk and co-workers achieveda na pparentq uantum yield (AQY) of 0.3 %u sing aR u II photosensitizer (PS) immobilized on the surface of aw ater reduction catalyst, Pt/ H x K 4Àx Nb 6 O 17 ,w ith iodide as ar edox-reversible electron donor. [38] In 2013, Abe et al reported overall water splitting (AQY = 0.05 %) using coumarin derivatives( NKX-2677) immobilized on Pt/H x K 4Àx Nb 6 O 17 as aw ater reductionD SP coupled with an O 2 evolution photocatalyst comprising IrO 2 -Pt/WO 3 and iodide redox mediator.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently light-driven water splitting mediated by photogenerated bromine, which activated a water oxidation catalyst, was studied employing the same sensitizer. 18 Usually, the absorber is linked to the semiconductor surface via an anchoring group, such as the carboxylic acid group forming a mono-or bidentate configuration depending on surface composition and structure. 19 Alternatively, dye− semiconductor interactions based on π-stacking/hydrophobic forces were reported.…”
Section: Introductionmentioning
confidence: 99%
“…A huge series of metal complexes or organic molecules was employed during recent years in conjunction with metal oxides: , recently, Meyer and co-workers reported an efficient ruthenium polypyridyl photocatalyst for hydrobromic acid splitting anchored on the surface of SnO 2 /TiO 2 core–shell nanostructures with two phosphonic groups. Concurrently light-driven water splitting mediated by photogenerated bromine, which activated a water oxidation catalyst, was studied employing the same sensitizer …”
Section: Introductionmentioning
confidence: 99%